The Healing Power of Nature: The Impact of Horticultural Therapy on Mental Health (Journal of Global Arts Studies, 2024)
Background: Horticultural therapy, which combines plant cultivation and natural environments, promotes individual physical and mental health as well as psychological growth. Although widely applied in countries such as Europe, America, and Japan, the exploration of this field in China is still in its infancy, necessitating the strengthening of theoretical research and practical application. Objective: This study aims to integrate domestic and international research on horticultural therapy through a literature review, revealing its mechanisms of action and practical effects, and providing theoretical and practical guidance for the development of horticultural therapy in China. Methods: A systematic review method was employed, searching relevant literature from the past decades in databases such as CNKI and Google Scholar. Keywords were used to filter the literature, excluding irrelevant or scientifically insufficient documents, with a focus on the psychological intervention effects of horticultural therapy on specific populations, such as Alzheimer's and autism patients. Results: The study found that horticultural therapy can effectively alleviate stress, reduce fatigue, and relieve anxiety, with positive psychological intervention effects on Alzheimer's and autism patients. Indoor plants can enhance happiness, promote relaxation, and decrease negative emotions. The application of plant metaphors in horticultural therapy provides a new perspective for psychotherapy. Conclusion: Horticultural therapy, as an adjunct treatment method, has development potential in China. Future research should focus on individualization and precision, exploring the variability of individual responses to horticultural therapy, and delve deeper into the application of plant metaphors to enhance the scientific and practical aspects of horticultural therapy, providing more effective pathways for individual mental health.
Keywords: Horticultural Therapy; Psychotherapy; Art Therapy; Natural Therapy